Comparable Complications but Fewer Reoperations with TIGR Matrix versus No Mesh in Implant-based Breast Reconstruction: a Long-term Retrospective Comparative Analysis - Alakortes, Henrietta (My University, 2026)
Implant-based breast reconstruction frequently utilizes mesh for support. While biological meshes are common, their high cost is a significant drawback. TIGR Matrix, a synthetic resorbable mesh, has emerged as a potential cost-effective alternative with promising early outcomes. This retrospective comparative study aimed to evaluate the clinical outcomes of TIGR Matrix versus no-mesh techniques in implant-based breast reconstruction. This retrospective study compared outcomes of implant-based breast reconstruction with and without TIGR Matrix in 138 patients treated in Turku University Hospital between 2009 and 2024. Demographic data, operative details, postoperative complications and oncologic history including treatments were analyzed. 65 of the 138 patients underwent reconstruction with TIGR Matrix and 73 reconstruction without mesh. The groups were generally comparable in terms of patient demographics and comorbidities, although the TIGR Matrix group had lower rates of radiotherapy, chemotherapy and lymphadenectomy. Operative time and hospital stay were longer in the TIGR Matrix group, and immediate reconstruction was more common. The overall complication rate did not differ significantly between the groups. However, the number of reoperative procedures per patient was significantly lower in the TIGR Matrix group. These findings suggest that the use of TIGR Matrix in implant-based reconstruction does not increase the overall risk of postoperative complications compared with implant-based reconstruction without mesh.
Keywords: synteettinen verkko; implanttipohjainen rekonstruktio; välitön rintarekonstruktio; kaksivaiheinen rekonstruktio; kudosvenytin; prepektoraalinen; retropektoraalinen; TIGR Matrix; postoperatiiviset komplikaatiot